2017
DOI: 10.18632/oncotarget.22135
|View full text |Cite
|
Sign up to set email alerts
|

Linking CREB function with altered metabolism in murine fibroblast-based model cell lines

Abstract: The cAMP-responsive element binding protein CREB is frequently overexpressed and activated in tumors of distinct histology, leading to enhanced proliferation, migration, invasion and angiogenesis as well as reduced apoptosis. The de-regulated expression of CREB might be linked with transcriptional as well as post-transcriptional regulation mechanisms. We show here that altered CREB expression levels and function are associated with changes in the cellular metabolism. Using comparative proteome-based analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Atf4 (Averous et al, 2004;Dey et al, 2012) binding sites was present within the 1000 bp upstream of TSS for 69% of the sequences, while a majority had at least one copy of Cebpa or Cebpb (Ramji and Foka, 2002;Pedersen et al, 2007;Dey et al, 2012) binding sites. Binding sites for the cAMP-responsive element binding protein (Creb1) (Kim et al, 2016;Steven et al, 2017) was found in one or two copies in Mfsd6, Mfsd8, Mfsd11, and Unc93b1, three to four copies in Slc22a32, Slc22b5, Slc33a2, Slc59a1, Slc60a1, Slc60a2, Mfsd9, and Mfsd14a, seven to eight copies in Unc93a. The novel regulator of metabolism, E2f1 (Denechaud et al, 2017), had predicted binding sites in 20 out of 29 transporters and 60% of them had more than three copies present, with the highest amount of copies in Mfsd11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atf4 (Averous et al, 2004;Dey et al, 2012) binding sites was present within the 1000 bp upstream of TSS for 69% of the sequences, while a majority had at least one copy of Cebpa or Cebpb (Ramji and Foka, 2002;Pedersen et al, 2007;Dey et al, 2012) binding sites. Binding sites for the cAMP-responsive element binding protein (Creb1) (Kim et al, 2016;Steven et al, 2017) was found in one or two copies in Mfsd6, Mfsd8, Mfsd11, and Unc93b1, three to four copies in Slc22a32, Slc22b5, Slc33a2, Slc59a1, Slc60a1, Slc60a2, Mfsd9, and Mfsd14a, seven to eight copies in Unc93a. The novel regulator of metabolism, E2f1 (Denechaud et al, 2017), had predicted binding sites in 20 out of 29 transporters and 60% of them had more than three copies present, with the highest amount of copies in Mfsd11.…”
Section: Resultsmentioning
confidence: 99%
“…Three promoter motifs, the TATA box, CCAAT box and the GC box were analyzed. The JASPER CORE 2018 vertebrate library was used to search for transcription factor motifs and several transcriptions factors known to be affected by macronutirent metabolism were analyzed; Atf4 (Averous et al, 2004;Dey et al, 2012), Cebpa (Pedersen et al, 2007), Cebpb (Ramji and Foka, 2002), Creb1 (Kim et al, 2016;Steven et al, 2017), E2f1 (Denechaud et al, 2017), FoxO1 (Kousteni, 2012), Mlx, Mlxip, and Mlxipl (Ma et al, 2006;Havula and Hietakangas, 2012).…”
Section: Promoter Sequences Analysismentioning
confidence: 99%
“…Surfen is an antagonist for heparan sulfate [110], and its potential CREB-CRE blocking mechanism was described by Rishi and coworkers (2005), who reported that Surfen has a higher specificity for CREB than for C/EBPβ (EC50 0.6 µM vs. 2.5 µM) [112]. Surfen at lower concentrations has been shown to block the binding of CREB to a CRE oligonucleotide, accompanied by reduced proliferation of BC cell lines [111].…”
Section: Creb-cre Inhibitors Targeting the Interaction Of Creb And Dnamentioning
confidence: 96%
“…was highly expressed in bovine embryonic cells suggesting its possible role in transcriptional regulation during early genome activation (Vigneault, McGraw, & Sirard, 2009). The gene CREB1 is also metabolically important as it mediates transcriptional responses to different stimuli such as hormones, growth factors and neurotransmitters (Steven et al, 2017). Adipose tissue coordinates the systemic insulin and modulates energy balance through CREB1, implying CREB1 plays an important role in glucose homeostasis and energy metabolism (Qi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%